Biogas power plant in kalipucang hamlet, bangunjiwo village, kasihan district, bantul regency - Muhammad Abdus Shomad; Sotya Anggoro (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Kalipucang hamlet is in Bangunjiwo Village and is home to 53 farmers from the “Andini Makmur” livestock farming group. The majority of the population works as cattle breeders, while others are farmers. The livestock farming group "Andhini Makmur" manages 80 cows in this village. The dung has only been dumped in the cage for a few months. Later, animal manure collectors buy it for a low price, if not for free. The lengthy sitting of the dung causes environmental pollution in the community, including air pollution and an unpleasant odor, and it can cause disease. The use of dung waste was a viable option for the prosperous farmer group. The conversion of livestock waste into electrical energy via a biogas process was a positive solution to livestock waste, which had been a major problem for the livestock community. The outcomes of the community service program carried out raised awareness among the “Andini Makmur” livestock group in particular, and the Kalipucang hamlet community in general, that livestock waste could be managed independently and produced electricity useful for lighting cages and moving water pumps at the livestock rearing site.